Aminomethylation of imidazopyridines using N, N-dimethylformamide as an aminomethylating reagent under Cu(II)-catalysis. Issue 49 (3rd December 2020) - Ghosh, Payel; Samanta, Sadhanendu; Ghosh, Sumit; Jana, Sourav; Hajra, Alakananda
Graphical abstract: Highlights: N, N -Dimethylformamide has been explored as an aminomethylating reagent. Synthesis of aminomethylated imidazo[1, 2- a ]pyridines under Cu(II)-catalysis. Selective functionalization of imidazo[1, 2- a ]pyridines at the C-3 position. Abstract: N, N -Dimethylformamide has been explored as an aminomethylating reagent in the functionalization of imidazopyridine under Cu(II)-catalysis. A library of aminomethylated imidazopyridines with broad functionalities was synthesized in good yields.